2006
DOI: 10.1038/sj.bmt.1705368
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells are susceptible to human herpesviruses, but viral DNA cannot be detected in the healthy seropositive individual

Abstract: Allogeneic stem cell transplantation is often complicated by reactivation of herpesviruses. Mesenchymal stem cells (MSC) are immunomodulatory and may be used to treat graft-versus-host disease. We investigated if herpesviruses infect and can be transmitted by MSC, and if MSC suppress immune responses to various infectious agents. Mesenchymal stem cells from healthy seropositive donors were evaluated with polymerase chain reaction for the most common herpesviruses: cytomegalovirus (CMV), herpes simplex virus ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 37 publications
5
75
0
1
Order By: Relevance
“…This raises interesting questions in regards to a possible stromal progenitor cell reservoir for latent HCMV or at the very least an amplification reservoir. 46 Sundin et al 33 show that ex vivo-expanded hMSCs from HCMV seropositive individuals displayed no signs of viral infection as measured by PCR. ASCs are regarded as immunoprivileged and their residence in the body's largest endocrine organ would be an ideal site for HCMV to influence host health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises interesting questions in regards to a possible stromal progenitor cell reservoir for latent HCMV or at the very least an amplification reservoir. 46 Sundin et al 33 show that ex vivo-expanded hMSCs from HCMV seropositive individuals displayed no signs of viral infection as measured by PCR. ASCs are regarded as immunoprivileged and their residence in the body's largest endocrine organ would be an ideal site for HCMV to influence host health.…”
Section: Discussionmentioning
confidence: 99%
“…24,[33][34][35] Although very similar, ASCs and hMSCs do display differences in regards to surface receptor repertoire and differentiation potential. 36,37 Additionally, these surface antigens can change within a cell type as a function of passage number and/or time in culture.…”
Section: Discussionmentioning
confidence: 99%
“…6 Indeed, some reports have indicated that MSCs are capable of suppressing pathogen-specific T-cell proliferation and effector function directed against herpesviruses in vitro. 7,8 However, data on the direct interaction between MSCs and microbial pathogens are sparse. Here, we demonstrate for the first time that on stimulation with inflammatory cytokines IDO-positive human MSCs exhibit a cell autonomous, broad-spectrum antimicrobial effector function directed against clinically relevant bacteria, protozoal parasites and viruses.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns were supported by in vitro observations that lymphocyte proliferation induced by herpesviruses is suppressed by MSCs. 40 A better understanding of the safety of MSCs will allow us to apply our basic knowledge of MSC biology to the design of clinical therapies. Further clinical trials to this end should be considered.…”
Section: Therapeutic Safety In Clinical Trials Of Msc Transplantationmentioning
confidence: 99%